2019
DOI: 10.1111/jce.14091
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of the origin and characteristics of gaseous microemboli during catheter electroporation ablation

Abstract: Introduction Recent studies demonstrated that irreversible electroporation (IRE) ablation may be an alternative method for thermal ablation for pulmonary vein isolation. Development of gaseous microemboli during catheter ablation might lead to asymptomatic ischemic events and is therefore an important research topic. Gas formation during arcing with direct current catheter ablation has been studied in the past, however not for nonarcing IRE‐ablation. Objective The aim of the present study was to visualize, qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…This can cause gas microemboli with consequent coronary occlusion, stroke or silent cerebral events. To our best knowledge, there is no systematic characterization of this phenomenon for therapies employing DC-PFA, with a notable exception for LifePak9 DCpulses which are characterized in vitro (van Es et al, 2019a). In our experience, DC pulse trains of microseconds can also produce gas bubble stream (Supplementary Video 4).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This can cause gas microemboli with consequent coronary occlusion, stroke or silent cerebral events. To our best knowledge, there is no systematic characterization of this phenomenon for therapies employing DC-PFA, with a notable exception for LifePak9 DCpulses which are characterized in vitro (van Es et al, 2019a). In our experience, DC pulse trains of microseconds can also produce gas bubble stream (Supplementary Video 4).…”
Section: Discussionmentioning
confidence: 90%
“…DC monophasic pulses are historically the most employed for electroporation of cell suspensions, but they can lead to potentially painful nerve and muscle capture (Mercadal et al, 2017), arcing, metallic release in solution (Meir and Rubinsky, 2014), and bubble stream formation, also due to electrolysis without arcing (van Es et al, 2019a). These issues require a careful control of DC pulses delivery and avoid direct galvanic coupling between electrodes and tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Monophasic or biphasic waveform can be used for pulse delivery. Monophasic waveform results in the greatest charging capacity of the cell membrane, creating the strongest damaging effects; however, it may carry the risk of electrically depolarizing surrounding tissues, inducing muscle contraction and gas formation 25,26 . Biphasic waveforms can greatly reduce muscle contraction but will generate weaker damaging effects 27 .…”
Section: Parameters Of Pef Deliverymentioning
confidence: 99%
“…While IRE overcomes many complications associated with thermal ablation techniques, it does pose some similar risks such as thrombosis, haemorrhage and infection, however these are common to all procedures employing similar access techniques [ 50 ]. Specific to IRE there is an associated risk of electrolysis when untuned current is passed through body fluids with dissolved electrolytes, instigating gas formation [ 97 , 98 ]. One study reported that different current polarity may decrease gas bubble formation as a side-effect of IRE, highlighting that a reduced number of gas bubbles are released when using anodal IRE, compared to RF or cathodal IRE [ 98 ].…”
Section: Electroporation As An Ablative Approachmentioning
confidence: 99%